Analysis of the Upregulated Expression Mechanism of Apoptotic Chromatin Condensation Inducer 1 in Hepatocellular Carcinoma Based on Bioinformatics - Tang, Yulian; Ni, Anni; Sun, Lishuang; Li, Shu; Li, Genliang (Turkish Journal of Gastroenterology, 2024)
Background/Aims: A large number of differentially expressed molecules exist in hepatocellular carcinoma (HCC), and the mechanism by which they upregulate or downregulate expression is still unclear. The purpose of this study is to explore the possible mechanism of differential expression of apoptotic chromatin condensation inducer 1 (Acin1) in HCC. Materials and Methods: A mouse HCC model was constructed, and the expression of Acin1 in HCC was analyzed by whole transcriptome sequencing, bioinformatics analysis, and reverse transcription-quantitative polymerase chain reaction, and differentially expressed Acin1-related genes were screened to construct a protein–protein interaction and competing endogenous RNA (ceRNA) network. The microRNA (miRNAs) targeting Acin1 were further predicted using online databases and finally compared with sequencing data. Results: The expression of Acin1 was significantly up-regulated in HCC compared to the paracancerous and healthy control groups (P < .001). The top 10 upregulated genes closely related to Acin1 (Slc3a2, Wiz, Srrm2, Akt1, Hnrnpu, Sap18b, Pabpn1, Ddx39b, Eif4a3, and Rnps1) were mainly involved in pathways such as messenger RNA (mRNA) surveillance, RNA transport, spliceosome, Janus kinase/ signal transducers and activators of transcription signaling, apoptosis, and ubiquitin-mediated proteolysis. The ceRNA network identified several molecules (2 long noncoding RNAs, 50 miRNAs, and 49 mRNAs) interacting with Acin1, among which miR-674-5p was highly expressed in all sample tissues, and higher than that of other differentially expressed miRNAs, and significantly downregulated in HCC. Multiple online databases such as miRWalk also predicted that miR-674-5p targets Acin1. This shows that miR-674-5p may be an important molecule for targeting Acin1. Conclusion: Acin1 is overexpressed in HCC, and the overexpressed Acin1 is most likely regulated by miR-674-5p and other ceRNA molecules Cite this article as: Tang Y, Ni A, Sun L, Li S, Li G. Analysis of the upregulated expression mechanism of Apoptotic chromatin condensation inducer 1 in hepatocellular carcinoma based on bioinformatics. Turk J Gastroenterol. 2024;35(4):307-315.